Dual Probe with Fluorescent and Magnetic Properties for Imaging Solid Tumor Xenografts - Liang Shan; Songping Wang; Rajagopalan Sridhar; Zaver M. Bhujwalla; Paul C. Wang (Molecular Imaging)
A dual probe with fluorescent and magnetic reporter groups was constructed by linkage of the near-infrared (NIR) fluorescent transferrin conjugate (Tf NIR ) on the surface of contrast agent-encapsulated cationic liposome (Lip-CA). This probe was used for magnetic resonance imaging (MRI) and optical imaging of MDA-MB-231-luc breast cancer cells grown as a monolayer in vitro and as solid tumor xenografts in nude mice. Confocal microscopy, optical imaging, and MRI showed a dramatic increase of in vitro cellular uptake of the fluorescent and magnetic reporter groups from the probe compared with the uptake of contrast agent or Lip-CA alone. Pretreatment with transferrin (Tf) blocked uptake of the probe reporters, indicating the importance and specificity of the Tf moiety for targeting. Intravenous administration of the dual probe to nude mice significantly enhanced the tumor contrast in MRI, and preferential accumulation of the fluorescent signal was clearly seen in NIR-based optical images. More interestingly, the contrast enhancement in MRI showed a heterogeneous pattern within tumors, which reflected the tumor's morphologic heterogeneity. These results indicate that the newly developed dual probe enhances the tumor image contrast and is superior to contrast agent alone for identifying the tumor pathologic features on the basis of MRI but also is suitable for NIR-based optical imaging.